Formation of dynamically transversely trapping surfaces and the stretched hoop conjecture. (15th May 2020) - Yoshino, Hirotaka; Izumi, Keisuke; Shiromizu, Tetsuya; Tomikawa, Yoshimune
Abstract: A dynamically transversely trapping surface (DTTS) is a new concept for an extension of a photon sphere that appropriately represents a strong gravity region and has close analogy with a trapped surface. We study formation of a marginally DTTS in time-symmetric, conformally flat initial data with two black holes, with a spindle-shaped source, and with a ring-shaped source, and clarify that C6π GM describes the condition for the DTTS formation well, where C is the circumference and M is the mass of the system. This indicates that an understanding analogous to the hoop conjecture for the horizon formation is possible. Exploring the ring system further, we find configurations where a marginally DTTS with the torus topology forms inside a marginally DTTS with the spherical topology, without being hidden by an apparent horizon. There also exist configurations where a marginally trapped surface with the torus topology forms inside a marginally trapped surface with the spherical topology, showing a further similarity between DTTSs and trapped surfaces.